Estimation of the reconstruction parameters for atom probe tomography - Gault, B; de Geuser, F; Stephenson, LT; Moody, M; Muddle, B; Ringer, S (2008)
The application of wide field-of-view detection systems to atom probe experiments emphasizes the importance of careful parameter selection in the tomographic reconstruction of the analyzed volume, as the sensitivity to errors rises steeply with increases in analysis dimensions. In this article, a self-consistent method is presented for the systematic determination of the main reconstruction parameters. In the proposed approach, the compression factor and the field factor are determined using geometrical projections from the desorption images. A three-dimensional Fourier transform is then applied to a series of reconstructions, and after comparing to the known material crystallography, the efficiency of the detector is estimated. The final results demonstrate a significant improvement in the accuracy of the reconstructed volumes. Copyright © Microscopy Society of America 2008.